Thermoplastic starch plasticized with alginate-glycerol mixtures:Melt-processing evaluation and film properties - Lopez, Olivia Valeria (2015)
Corn starch melt-processing in the presence of a commonly used plasticizer mixture (water/glycerol)and a non-conventional alternative (alginate/glycerol) was evaluated. All assayed formulations weresuccessfully processed by melt-mixing and injected in circular probes. It was determined that all samples presented a typical viscoelastic behavior, observing a decrease in storage and loss modulus withwater and alginate concentration, which facilitated samples processability. Concerning to thermal sta-bility, it was not affected neither for water nor alginate presence. From injected probes, flexible filmswere obtained by thermo-compression. Films with the highest assayed water content presented a stickyappearance, whereas those containing alginate were non-tacky. Plasticizing action of water and alginatewas evidenced by the occurrence of homogeneous fracture surfaces, without the presence of unmeltedstarch granules. Besides, the shift of glass transition temperature to lower values also corroborated theplasticizing effect of both additives. In conclusion, obtained results demonstrated the well-plasticizingaction of sodium alginate on starch matrix, turning this additive into a promissory alternative to replacewater during melt-processing of thermoplastic corn-starch.